Relationship between Circadian Types and Nurses' Caring Behaviors - H Mohammadi; M Seyedshohadai; N Seyedfatemi; A Mehran (Iran University of Medical Sciences, 2014)
Abstract   Background & Aim: Caring is the nature of nursing and plays an important role in the promotion of patients' health level, process of recovery and their satisfaction. Difference in the performance and behavior among circadian types may influence nurses' performance such as caring for patients. Accordingly, this study aims to determine the relationship between circadian types and nurses' caring behaviors.   Material & Methods: This is a descriptive-correlational study. A total of 573 nurses were selected from different wards of hospitals affiliated to Tehran University of Medical Sciences through cluster sampling. Data was collected by Morningness Eveningness Questionnaire (MEQ) and Caring Behaviors Inventory (CBI) and analyzed by Spearman test and partial correlation using SPSS-PC (v. 16).   Results: The findings showed that most of the sample (%57.9) was of intermediate type. Subscales of professional knowledge and skill, and positive connectedness from CBI had the most and least scores respectively. After adjustment for age and work experience, there was no significant association between circadian types and caring behaviors. Conclusion: The results did not provide enough evidence regarding the existence of a relationship between circadian types and nurse caring behaviors. Accordingly, conducting a same study by controlling the variables of age and work experience is recommended.